VD_FINDINFO HC / 2014 / 53 vom 6. Dezember 2013 - VD Tribunal cantonal (2013)
DÉPENS, RETRAITVOIE DE DROIT, HONORAIRES, AVOCAT | 106 al. 1 CPC (CH), 95 al. 1 CPC (CH), 95 al. 1 let. b CPC (CH), 95 al. 3 let. b CPC (CH)